Microbiological Quality of Ready to Eat Salads Sold in the Klang Valley Region of Malaysia - Icah ardani purba; Muhammad Said Siregar; Nur Ilida Binti Mohamad; Rahimah Mohd Zaki; Yangmurni Zamani (Journal of Global Sustainable Agriculture, 2026)
Ready-to-eat salads have become increasingly popular as a convenient and healthy food option; however, they are prone to microbiological contamination due to minimal processing and the absence of heat treatment. This study aimed to evaluate the microbiological quality of ready-to-eat salads sold in the Klang Valley, Malaysia. A total of ten samples from various brands were analyzed using Total Plate Count (TPC), Total Yeast and Mould Count (TYMC), and Total Coliform methods. The results showed that TPC values ranged from 4.49 to 6.60 Log CFU/g, with some samples approaching or exceeding the acceptable safety limit. TYMC values ranged from 0.00 to 3.11 Log CFU/g, with the highest value observed in sample F10, indicating potential yeast and mould growth due to high moisture and nutrient content. Coliforms were detected in several samples, with the highest value of 4.03 Log CFU/g, suggesting possible post-processing contamination or inadequate sanitation practices. Overall, most products complied with food safety standards; however, improvements in Good Manufacturing Practices (GMP) and cold chain temperature control are necessary to ensure microbiological quality.